2022
DOI: 10.1093/jrs/feac059
|View full text |Cite
|
Sign up to set email alerts
|

At the Crossroads between Care and Control: A Cross-Country Comparison of Assisted Return

Abstract: Assisted return (AR) is a widespread policy tool offering financial support and counselling to returning migrants. Policymakers present it as a durable solution vis-à-vis undocumented migrants and rejected asylum seekers. However, AR has been proven to display the concurrence of care and control typical of contested humanitarianism. This concurrence takes different shapes across nation states. Our paper looks at how Sweden, Finland, the UK, Italy, Spain, and Portugal concretely configure care and control in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The crucial difference is that these are successful migrants who, as such, do not require AVRR programmes in order to return to their homeland. Indeed, as already emphasised, those who return home under AVRR programmes are generally vulnerable people with very limited resources and professional and entrepreneurial skills at their disposal; at the most, they will—as confirmed by our study—make use of these programmes to set up small businesses which, apart from rare exceptions, can at best provide for the returnee's basic essentials for survival (Marino et al., 2022: 2).
[We have often helped] people who have recently left reception centres because the period has expired. Even people who were simply tired of remaining in Italy after so many years because they no longer saw a future, there was no work, they were on the streets or in reception centres and, when they learned of the AVRR opportunity, they thought about it seriously.
…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The crucial difference is that these are successful migrants who, as such, do not require AVRR programmes in order to return to their homeland. Indeed, as already emphasised, those who return home under AVRR programmes are generally vulnerable people with very limited resources and professional and entrepreneurial skills at their disposal; at the most, they will—as confirmed by our study—make use of these programmes to set up small businesses which, apart from rare exceptions, can at best provide for the returnee's basic essentials for survival (Marino et al., 2022: 2).
[We have often helped] people who have recently left reception centres because the period has expired. Even people who were simply tired of remaining in Italy after so many years because they no longer saw a future, there was no work, they were on the streets or in reception centres and, when they learned of the AVRR opportunity, they thought about it seriously.
…”
Section: Discussionsupporting
confidence: 66%
“…Moving beyond the initial research questions, we can develop a further concluding reflection on how the issue of repatriation is increasingly being associated with the idea that returning migrants can contribute significantly to the development of their country of origin. The relationship between return migration and development is now supported by a variety of empirical evidence (Faist et al., 2011) and is sometimes brought up by policymakers as an additional incentive to promote AVRR programmes, as well as garner the cooperation of recipient countries in implementing them (Marino et al., 2022: 2). However, in the specific case of AVRR, this link – if indeed it exists at all – is incredibly tenuous, as our research project also revealed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations